A versatile methodology for preventing a parallel transmission system using impedance-based techniques - Mohan P. Thakre; Rakesh Shriwastava; Rahul G. Mapari; Deepak Prakash Kadam; Sunil Somnath Kadlag (Bulletin of Electrical Engineering and Informatics, 2023)
The various configurations that exist for a compatible circuit depend on an object, such as operating conditions, the occurrence of an inter-circuit error and the result of the coupling of the transmission line. This feature makes the protection of the same transmission lines very difficult. This paper introduces a new algorithm based on a state diagram that contains location data collected on a passing bus. Combine the different separation processes and the impedance-based process is used. The classification process cannot detect internal errors and only compares with existing phases where the same regional error occurs in the 2D space and the impedance-based method used to cover the resulting error. The proposed algorithm incorporates impedance-based methodology and separation technology to provide the appropriate response under all operating conditions of the same circuits.